Lipid rafts and clathrin cooperate in the internalization of PrP in epithelial FRT cells. - Daniela Sarnataro; Anna Caputo; Philippe Casanova; Claudia Puri; Simona Paladino; Simona S Tivodar; Vincenza Campana; Carlo Tacchetti; Chiara Zurzolo (PLoS ONE)
Background The cellular prion protein (PrP(C)) plays a key role in the pathogenesis of Transmissible Spongiform Encephalopathies in which the protein undergoes post-translational conversion to the infectious form (PrP(Sc)). Although endocytosis appears to be required for this conversion, the mechanism of PrP(C) internalization is still debated, as caveolae/raft- and clathrin-dependent processes have all been reported to be involved. Methodology/principal findings We have investigated the mechanism of PrP(C) endocytosis in Fischer Rat Thyroid (FRT) cells, which lack caveolin-1 (cav-1) and caveolae, and in FRT/cav-1 cells which form functional caveolae. We show that PrP(C) internalization requires activated Cdc-42 and is sensitive to cholesterol depletion but not to cav-1 expression suggesting a role for rafts but not for caveolae in PrP(C) endocytosis. PrP(C) internalization is also affected by knock down of clathrin and by the expression of dominant negative Eps15 and Dynamin 2 mutants, indicating the involvement of a clathrin-dependent pathway. Notably, PrP(C) co-immunoprecipitates with clathrin and remains associated with detergent-insoluble microdomains during internalization thus indicating that PrP(C) can enter the cell via multiple pathways and that rafts and clathrin cooperate in its internalization. Conclusions/significance These findings are of particular interest if we consider that the internalization route/s undertaken by PrP(C) can be crucial for the ability of different prion strains to infect and to replicate in different cell lines.